The corepressor NCOR1 regulates the survival of single-positive thymocytes. Issue 1 (December 2017) - Müller, Lena; Hainberger, Daniela; Stolz, Valentina; Hamminger, Patricia; Hassan, Hammad; Preglej, Teresa; Boucheron, Nicole; Sakaguchi, Shinya; Wiegers, G.; Villunger, Andreas; Auwerx, Johan; Ellmeier, Wilfried
Abstract Nuclear receptor corepressor 1 (NCOR1) is a transcriptional regulator bridging repressive chromatin modifying enzymes with transcription factors. NCOR1 regulates many biological processes, however its role in T cells is not known. Here we show thatCd4 -Cre-mediated deletion of NCOR1 (NCOR1 cKOCd4 ) resulted in a reduction of peripheral T cell numbers due to a decrease in single-positive (SP) thymocytes. In contrast, double-positive (DP) thymocyte numbers were not affected in the absence of NCOR1. The reduction in SP cells was due to diminished survival of NCOR1-null postselection TCRβhi CD69+ and mature TCRβhi CD69− thymocytes. NCOR1-null thymocytes expressed elevated levels of the pro-apoptotic factor BIM and showed a higher fraction of cleaved caspase 3-positive cells upon TCR stimulationex vivo . However, staphylococcal enterotoxin B (SEB)-mediated deletion of Vβ8+ CD4SP thymocytes was normal, suggesting that negative selection is not altered in the absence of NCOR1. Finally, transgenic expression of the pro-survival protein BCL2 restored the population of CD69+ thymocytes in NCOR1 cKOCd4 mice to a similar percentage as observed in WT mice. Together, these data identify NCOR1 as a crucial regulator of the survival of SP thymocytes and revealed that NCOR1 is essential for the proper generation of the peripheral T cell pool.